2020
DOI: 10.1002/adom.202000107
|View full text |Cite
|
Sign up to set email alerts
|

Phototuning Energy Transfer in Self‐Organized Luminescent Helical Superstructures for Photonic Applications

Abstract: Stimuli‐triggered changes in the emission color of functional materials are in demand for a variety of potential applications. Herein, a strategy to reversibly phototune fluorescence color in cholesteric liquid crystal (CLC) with self‐organized luminescent helical superstructure via fluorescence resonance energy transfer (FRET) is developed. This dynamic FRET system is constructed by doping with 1,2‐dithienyldicyanoethene‐based chiral fluorescent photoswitch (switch 7) as an acceptor and a conventional coumari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 59 publications
0
43
0
Order By: Relevance
“…In the past several years, there have been more and more reports on chiral emissive liquid crystals (N*-LCs) as CPL-active materials. These materials can self-assemble as highly regular helical arrangement in LC medium after annealing treatment as a result of the LC-templated molecular reorientation, which is beneficial for the enlarged effect of the induced CPL signals [101][102][103][104][105][106][107]. In 2020, Cheng's group [101] realized the recyclable CPL response behavior in N*-LCs doped with the axially chiral molecules (R/S)-37 (Figure 12a).…”
Section: Cpl-active Liquid Crystals and Liquidsmentioning
confidence: 99%
“…In the past several years, there have been more and more reports on chiral emissive liquid crystals (N*-LCs) as CPL-active materials. These materials can self-assemble as highly regular helical arrangement in LC medium after annealing treatment as a result of the LC-templated molecular reorientation, which is beneficial for the enlarged effect of the induced CPL signals [101][102][103][104][105][106][107]. In 2020, Cheng's group [101] realized the recyclable CPL response behavior in N*-LCs doped with the axially chiral molecules (R/S)-37 (Figure 12a).…”
Section: Cpl-active Liquid Crystals and Liquidsmentioning
confidence: 99%
“…Our group has reported several photosensitive CLCs based on chiral fluorescence photoswitches. [101][102][103][104][105][106][107] These photoswitches can undergo Z/E isomerization upon light irradiation, where the helical twisted power (HTP) value and fluorescence intensity vary between photostationary states (PSSs). For instance, by doping visible-light-driven chiral fluorescent molecular switch 4 into a nematic LC, a cholesteric phase was efficiently induced, which enabled strong CPL emission at 581 nm (Figure 10A).…”
Section: Light Irradiationmentioning
confidence: 99%
“…The inversion in the sign of CPL and the tuning of CPL wavelength could be achieved (Zheng et al, 2018 ; He et al, 2019 ). Moreover, suitably designed fluorescence resonance energy transfer (FRET) and charge transfer systems have also been used to tailor the CPL emission using * NLC templates (Li et al, 2020 ; Lin et al, 2020 ). Thus, it is observed that doping achiral fluorescent dyes with * NLC is emerging as an effortless and efficient way of generating CPL active materials.…”
Section: Liquid Crystalsmentioning
confidence: 99%